If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -6)(x + 10) = 0 Reorder the terms: (-6 + 5x)(x + 10) = 0 Reorder the terms: (-6 + 5x)(10 + x) = 0 Multiply (-6 + 5x) * (10 + x) (-6(10 + x) + 5x * (10 + x)) = 0 ((10 * -6 + x * -6) + 5x * (10 + x)) = 0 ((-60 + -6x) + 5x * (10 + x)) = 0 (-60 + -6x + (10 * 5x + x * 5x)) = 0 (-60 + -6x + (50x + 5x2)) = 0 Combine like terms: -6x + 50x = 44x (-60 + 44x + 5x2) = 0 Solving -60 + 44x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (-10 + -1x)(6 + -5x) = 0Subproblem 1
Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10Subproblem 2
Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2Solution
x = {-10, 1.2}
| 75q=3756 | | -6x-6-7=-13 | | -2(x-9)=-34 | | 8b=96 | | 4k-5k-4k= | | 17g=981 | | 4x^3-2x^3= | | -5=q^7 | | 30=12x-4+10x-10 | | -14x=-336 | | 3x-9/5=6 | | .75z+6= | | 3(y-4)=(3y-5-4y)-(2-5y+10) | | 6.6g+4=4.6g+8 | | 75=3x+2+10x-5 | | 1/3-4/x=2-3/2x | | 7x-10+28+2x=-5 | | 5b=2.000 | | Y=2x^4+18x^3+40x^2+24x | | y+708=1179 | | (6gk)/(3k^2) | | 2w-3= | | 1/6/54 | | 6gk/3k^2 | | 234+y=123 | | 102=6y | | 8m+3(n+7m)-n= | | 2b^2=9b+45 | | 28.33=-12w | | 5a+10=5-a | | 3-3x=-18 | | x+256=-412 |